Enzyme Inhibitory Properties and Antimicrobial Activity of Geranium tuberosum Methanol Extract - Almaz, Züleyha (My University, 2023)
Geranium tuberosum roots are consumed fresh in some areas of the countryside of Turkey. This study was conducted to scientifically validate the traditional use of the species. The enzyme inhibition effect and antimicrobial activity of the root and leaf parts of Geranium tuberosum were investigated using a methanol extract. The leaf extract had higher acetylcholinesterase and butyrylcholinesterase activity than the root extract, while the root extract showed a stronger inhibitory effect on xanthine oxidase enzyme.. Also, the antifungal and antibacterial activities of the extracts were investigated using the hollow agar technique. It was observed that both extracts gave high antimicrobial activity on different bacterial strains. These results confirmed that Geranium tuberosum is a natural antibacterial, and has enzyme inhibitory potential.
Keywords: Geranium tuberosum; Acetylcholinesterase; Antimicrobial; Xanthine Oxidase; Butyrylcholinesterase